The paradox of care in behavioral epigenetics: Constructing early-life adversity in the lab - Lappé, Martine (Biosocieties, 2018)
Many epigenetic studies focus on how stress, trauma, and care become molecularly embodied, affect gene expression without changing DNA sequence, and produce changes that influence the health and behavior of individuals, their offspring, and future generations. This article describes how care has become central in research on the epigenetic effects of early-life adversity. My analysis draws on two years of ethnographic research in a behavioral epigenetics laboratory in the United States. Building on traditions in feminist theory and the sociology of science, I document how care is enacted with research samples, experimental protocols, and behavioral endpoints in experiments with model organisms. My findings point to tensions between researchers’ care for the data and their measurement of adversity as a discrete variable in the form of maternal interaction, neglect, and abuse. I argue that these tensions suggest a “paradox of care” that is actively shaping how epigenetic knowledge is produced and its impacts in society. My analysis shows how decisions in the lab are shaping new understandings of how early-life experiences influence health, with significant impacts on our expectations of mothers and pregnant women. This study suggests that the more complex explanations of health and development promised by epigenetics are simultaneously constructed and constrained by caring practices in the laboratory.